Using a realist approach in understanding youth offending service delivery requirements for young people who offend with speech, language and communication needs in England - Sam Redgate; Wendy Dyer; Michael A. Smith (Springer, 2022)
Abstract Research consistently demonstrates the over-representation of young people with speech, language and communication needs within the youth criminal justice system, with estimates suggesting this population accounts for up to 90% of young people who offend. Acknowledgement and understanding of these individual-based needs, along with identified service delivery adaptation(s) (where necessary) are required to ensure all young people, regardless of needs experienced, can effectively engage with, and have their voices heard, within the context of Youth Offending Services. By using a realist approach, qualitative interviews with stakeholders (n = 15) are used to explore service conditions required to incorporate speech, language and communication provision within a Youth Offending Service. Specifically, the research provides original and significant insights into the interconnections between understanding of speech, language and communication, service delivery models and engagement with young people. Seven themes pertaining to delivery requirements within youth offending settings were identified. From these themes, explanations in the form of programme theories are postulated detailing core service delivery conditions required in youth offending settings to address speech, language and communication need. These include, increased understanding of speech, language and communication; unpicking terminology and becoming communication friendly; staff cohesion prompting learning together; and co-construction approach to service delivery. The core approach underpinning these postulated programme theories was an increased awareness of speech, language and communication issues by youth offending staff. This increased awareness is evidenced to lead to an adaptation of behaviours and practices by staff which in turn increases engagement with young people.